Penerapan media wordwall non-digital untuk mengembangkan kemampuan kognitif siswa pada pembelajaran bahasa Indonesia di Madrasah ibtidaiyah - Silvana Mei Devita; Jamilatun Nafi'ah (Universitas Negeri Semarang, 2026)
This study aims to describe the implementation of non-digital Wordwall media in Indonesian language learning and to examine the process of developing students’ cognitive abilities in Madrasah Ibtidaiyah. The research employed a qualitative approach with a case study design. Data were collected through classroom observation, interviews with the Indonesian language teacher and students, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through technique and source triangulation. The findings indicate that non-digital Wordwall media can be effectively implemented in learning because it is easy to use and does not rely on digital technology. The use of this media helps teachers present material concretely and encourages student engagement in learning activities. Learning processes involving activities such as arranging words and responding directly to questions contribute to the development of students’ cognitive abilities, particularly in understanding and processing language material. In addition, students’ responses to the use of the media were positive, showing increased enthusiasm, participation, and interest in learning.This study concludes that non-digital Wordwall media is a relevant alternative instructional medium to support active, meaningful Indonesian language learning that aligns with the developmental characteristics of Madrasah Ibtidaiyah students.